Effectiveness of natural lip balm cinnamon (Cinnamomum burmannii) in accelerating the incision wound healing process in rattus norvegicus - Damayanti, Meta Maulida; Sari, Ajeng Kartika; Furqaani, Annisa Rahmah (Padjadjaran Journal of Dentistry, 2022)
ABSTRACT Introduction: Cinnamomum burmannii is commonly used in the treatment and is thought to be an anti-inflammation medicinal herb that may hasten recovery. Lip wound healing is a critical need for aesthetic performance. The purpose of this study is to evaluate the efficacy of natural lip balm C. Burmannii has been shown to speed up the healing of incision wounds in rats (Rattus norvegicus). Methods: This research was carried out in the laboratory biomedical Faculty of Medicine, Universitas Islam Bandung. In twenty-seven male rats weighing 200-300 g, a lip mucous incision of 10 mm length and 4 mm depth was surgically created. Simple random sampling was used to divide the animals into three treatment groups based on wound treatment after lip incision (The control group applied distillation water, the first group applied a lip balm placebo/base, and the second group applied natural lip balm C. burmannii) and then divided into three observation times (days 3rd, 7th, and14th). A lip biopsy was performed during each observation time to determine the success of the therapy. The macroscopic examination was carried out by counting the number of lip wounds that were closed around, while the microscopic examination was carried out by counting epithelialization with a Leica microscope and image raster software. Result: The length of the lip wound has greatly decreased in the C. Burmannii group with a p-value of 0,048 (p<0.05, and epithelialization was comparable across the board. Conclusion: The use of Cinnamomum burmannii natural lip balm is effective in accelerating lip wound healing by bringing the lip wound closer together. Effectiveness of Natural lip balm Cinnamon (Cinnamomum burmannii) in accelerating the incision wound healing process in Rattus norvegicus.Keywords: natural lip balm cinnamomum burmannii; wound closer; epithelialization